RANCANG BANGUN SISTEM INFORMASI PERKEBUNAN KELAPA SAWIT BERBASIS WEB UNTUK MENDUKUNG PELAPORAN HASIL KERJA (STUDI KASUS: PERKEBUNAN PALM NBH SEJAHTERA) - Yulianus Palopak; Kurnia Rahmat (TeIKa, 2017)
The purpose of this study is to analyze and design the needs of information system in the plantation industry, especially for palm plantation to perform planning, execution and reporting of daily work activities. The methodology used in this research is SDLC (System Development Life Cycle), by applying Waterfall model that consist of stages such as: Analysis; Design; Implementation; Testing; and Maintenance. The result of this research is a design of information system that can be used in palm plantation company to help to manage data and reporting for their activities such as spraying, clearing, fertilizing and harvesting of palm. It is expected that the results of this design can be implemented directly in the real situation so that it can be known of the effectiveness and efficiency of the system.